Pathogen Recognition in the Human Female Reproductive Tract: Expression of Intracellular Cytosolic Sensors NOD1, NOD2, RIG‐1, and MDA5 and response to HIV‐1 and Neisseria gonorrhea. (17th September 2012) - Ghosh, Mimi; Shen, Zheng; Fahey, John V.; Crist, Sarah G.; Patel, Mickey; Smith, Jennifer M.; Wira, Charles R.
<x xml:space="preserve">Abstract</x> Problem Expression patterns and regulation of cytosolic pattern recognition receptors (PRR) NOD‐1, NOD‐2, RIG‐1, and MDA5 have not been elucidated in the human female reproductive tract (FRT). Method of study Primary epithelial cells (EC) isolated from Fallopian tube (FT), endometrium (EM), cervix (Cx), and ectocervix (Ecx) were treated with estradiol, poly(I:C), Neisseria gonorrhea (GC), and HIV‐1. PRR mRNA expressions were analyzed by Real‐time RT‐PCR. Conditioned media were analyzed for IL‐8 by ELISA. Results EC from all FRT compartments constitutively expressed NOD1, NOD2, RIG‐1, and MDA5 with highest levels expressed by FT. Stimulation with poly(I:C) resulted in upregulation of NOD2, RIG‐1, and MDA5 in all FRT compartments and correlated with increased secretion of IL‐8, whereas estradiol treatment had no effects. Exposure to GC and HIV‐1 IIIB but not BaL resulted in selective upregulation of NOD2 and MDA5. Conclusion PRR are expressed throughout the FRT and differentially regulated by poly(I:C), GC and HIV‐1.